MEMPERTIMBANGKAN PERSPEKTIF SERVICE-DOMINANT LOGIC SEBAGAI STRATEGI PEMASARAN DI AGRO TAWON WISATA PETIK MADU, LAWANG - Zalyus, Firda Melani; Abdillah, Yusri; Iqbal, Mohammad (Profit: Jurnal Adminsitrasi Bisnis, 2020)
The Service-Dominant Logic (SDL) concept was first promoted by Vargo & Lusch (2004a) because of a shift in marketing perspective that prioritizes services in the exchange process. The SDL marketing perspective consists of eight aspects namely, operant resources, resourcing, service and experience, dialogue, value plans, value creation networks, learning through exchanges and marketing collaboration. This study examines the extent to which the Honey Picking Tourism Honey Agro (WPM) has implemented marketing perspectives according to the SDL concept. Data obtained through observation, interviews and documentation studies. The resource persons consisted of managers, division heads and WPM customers. Data analysis uses an interactive model (Miles, Huberman & Saldana, 2014) which starts from Data Collection, Data Condensation, Data Display, and Conclusion Drawing. The results showed that WPM has applied all eight aspects of the marketing perspective that are in accordance with the SDL concept. WPM Managers place customers as an internal part in value creation. This can be seen from the involvement of customers from the beginning of the formation of educational tourism to the ongoing development. Managers give priority to service to customers to meet customer needs and satisfaction. However, WPM applies the service concept without knowing the SDL concept in theory. So that the benefits obtained are more optimal for the application of the service concept, it is better for WPM to carry out theoretical learning about the SDL concept.Â